2019
DOI: 10.1186/s40100-019-0141-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Income Stabilization Tool on farm income level, variability and concentration in Italian agriculture

Abstract: This paper provides an ex ante assessment of the effects of the Income Stabilization Tool (IST), a new risk management tool proposed in the Common Agricultural Policy of the European Union. We investigate the effects of IST on income variability and levels as well as on income inequality in the farming population. We take Italian agriculture as an example as the introduction of IST is currently under discussion there. A rich panel of 2777 farms was studied over a period of 7 years. We use stochastic simulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 32 publications
7
29
0
Order By: Relevance
“…The results reveal that 1 percent increase in agriculture activities reduces income inequality by 0.7 percent. Similar result was obtained by Severini et al (2019), who used stochastic simulations to examine the relationship income inequality and agriculture in Italy. The authors found that farmers who used income stabilizers managed to reduce income inequality compared to those who did not use income stabilizers.…”
Section: Brics Stylized Factssupporting
confidence: 80%
“…The results reveal that 1 percent increase in agriculture activities reduces income inequality by 0.7 percent. Similar result was obtained by Severini et al (2019), who used stochastic simulations to examine the relationship income inequality and agriculture in Italy. The authors found that farmers who used income stabilizers managed to reduce income inequality compared to those who did not use income stabilizers.…”
Section: Brics Stylized Factssupporting
confidence: 80%
“…The year 2019 registered an increase of over 11%, demonstrating that this is a relevant topic for academics. This exponential growth is linked with the necessity to investigate the effects of PAC 2014-2020, and to determine the scientific soundness for the implementation of the new PAC 2021-2017 [26][27][28]. The analysis of the references cited is developed in two stages.…”
Section: Documents' Analysismentioning
confidence: 99%
“…Even insurance schemes for revenues or even income levels exist (e.g. Severini et al ., 2019). Most common insurance schemes that cover weather‐related damages are indemnity insurances.…”
Section: Agricultural Weather Insurancesmentioning
confidence: 99%
“…These can for example be insurance solutions at the level of revenues or incomes (e.g. Severini et al ., 2019) and insurance solutions that base payoffs on the occurrence of an adverse weather event instead of on damages (i.e. index insurances, Box 1) because insurance payoffs may not be linked to outcomes of specific farm activities.…”
Section: Agricultural Weather Insurancesmentioning
confidence: 99%